2015
DOI: 10.1007/s10620-015-3840-4
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Electrical Stimulation and Sacral Electrical Stimulation: A Long-Term Follow-Up Study of Dual-Device Treatment

Abstract: Aims The objective of this study was to investigate sacral electrical stimulation (SES) and gastric electrical stimulation (GES) by comparing upper and lower gastrointestinal (GI) and genitourinary (GU) symptoms and quality of life, before treatment and in the long term after treatment. We hypothesized that dual-device treatment would greatly improve upper and lower gastrointestinal and genitourinary symptoms, as well as quality of life. Methods Fifty-four patients who underwent dual-device treatment (GES an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Older work has shown that GES can also improve pancreatic function in patients with the symptoms of gastroparesis, likely via a vagal mechanism . Recent work with temporary and permanent GES has reported an effect on the small bowel and colon . However, one randomized sensory study did not reveal a central effect of GES in humans .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older work has shown that GES can also improve pancreatic function in patients with the symptoms of gastroparesis, likely via a vagal mechanism . Recent work with temporary and permanent GES has reported an effect on the small bowel and colon . However, one randomized sensory study did not reveal a central effect of GES in humans .…”
Section: Discussionmentioning
confidence: 99%
“…14 Recent work with temporary and permanent GES has reported an effect on the small bowel 40 and colon. 35,41 However, one randomized sensory study did not reveal a central effect of GES in humans. 42 Other work, however, a Linear regression was used with the change in GCSI total score as an outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Newer studies have elucidated the effects of GES on the mid gut and hind gut. In a 2016 study [31], 54 patients who underwent dual-device treatment (GES and sacral electrical stimulation) were followed for 24 months. With combined treatment, a statistically significant improvement was seen in upper GI, lower GI and genitourinary symptoms as well as quality of life.…”
Section: Mid-gut and Hind-gut Effectmentioning
confidence: 99%
“…Although the pathophysiology of motility disorders is not fully understood, impaired GI electrical activity is frequently correlated [3-8]. Studies have shown that GI electrical activity is measurable with smooth-muscle electromyography (EMG) and that GI motility can be modified with electrical stimulation (ES) [9-14]. Thus, a multilocular ES of the GI tract may be a promising mid- or long-term therapy for medically refractory GI motility disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a multilocular ES of the GI tract may be a promising mid- or long-term therapy for medically refractory GI motility disorders. However, to date, few studies have investigated the effects of multilocular ES in multiple segments of the GI tract in animals or humans [12-14]. We recently described successful modulation of electrical activity in 5 GI segments using variable ES [15].…”
Section: Introductionmentioning
confidence: 99%